Differences In The Effect Of Flash Card And Video Models On The Level Of Knowledge, Attitude And Compliance Of Pregnant Women In Consuming FE Tablets In Preventing Anemia In UPT Sindang Danau Community Health Center - Ulfia Fitrianingsih; Indah Eriska; Ika Lorenza (International Journal of Health Engineering and Technology, 2026)
Anemia is a condition in which the number of red blood cells decreases to meet the body's physiological needs. Anemia can be caused by a lack of nutrients that play a role in red blood cell formation. Anemia during pregnancy can cause complications that negatively impact both the mother and the fetus. Factors that can influence anemia include adherence to iron tablet consumption, which is related to the level of knowledge and attitudes of pregnant women regarding iron tablet consumption. The better the knowledge and attitudes of pregnant women, the better their adherence to iron tablet consumption to prevent anemia during pregnancy, and vice versa. This study aimed to determine whether education about anemia for pregnant women through flashcards and videos could improve the knowledge, attitudes, and adherence of pregnant women regarding iron tablet consumption to prevent anemia. This study was conducted from November to December 2025. This quantitative study used a pre-experimental design with a one-group pretest-posttest design. The sampling technique used was purposive sampling. The sample size for this study was 30 respondents. The instrument used was a questionnaire to assess knowledge, attitudes, and adherence to iron tablet consumption. The statistical test results using the non-parametric Wilcoxon test using SPSS obtained an Asymp. Sig. value of 0.000 or a p-value of <0.05, indicating a difference in the level of knowledge, attitudes, and compliance of pregnant women before and after being provided with counseling using flash cards and videos at the Sindang Danau Community Health Center. It can be concluded that there is a significant difference in the level of knowledge, attitudes, and compliance of pregnant women before and after being provided with counseling using flash cards and videos at the Sindang Danau Community Health Center.